Ã˜Â¯Ã™Ë†Ã˜Â± Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™Å Ã˜Â© Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ˜Â¥Ã™â€ Ã™â€¦Ã˜Â§Ã˜Â¡ Ã˜Â§Ã™â€žÃ˜Â®Ã™â€žÃ™â€šÃ™Å Ã™â€žÃ™â€žÃ˜Â´Ã˜Â¹Ã˜Â¨ (Ã˜Â¯Ã˜Â±Ã˜Â§Ã˜Â³Ã˜Â© Ã˜Â¹Ã™â€žÃ™â€° Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦ Ã™Ë†Ã˜Â¯Ã™Ë†Ã˜Â±Ã™â€¡ Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ˜Â¥Ã™â€ Ã™â€¦Ã˜Â§Ã˜Â¡ Ã˜Â§Ã™â€žÃ™â€šÃ™Ë†Ã™â€¦Ã™Å Ã˜Â¨Ã˜Â¥Ã™â€ Ã˜Â¯Ã™Ë†Ã™â€ Ã™Å Ã˜Â³Ã™Å Ã˜Â§) - ZA, Tabrani (Ar Raniry : International Journal of Islamic Studies, 2017)
Islam as a religion of rahmatan li al'alamin, very much its contribution to the national development which is oriented to the whole human development. The presence of religion is always accompanied by "two faces". On the one hand, inherently religion has an identity that is exclusive, particularistic, and primordial. At the same time, however, it is also rich in inclusive, Universalist and transcending identities. In its role as a directive system, religion is placed as the main reference in the process of change. Religion will serve as a supreme morality that provides the basis and strength of the society's spiritual elite as they dialectics with change. Likewise as a defensive system, religion becomes a kind of resistance force for society when it is in an increasingly complex circle of life issues amid the rapid flow of change. Islamic education as agents of social change that is in the atmosphere of modernization and globalization today is required to be able to play its role dynamically and proactively, both at the theoretical and practical intellectual level. Islamic education is not just a process of cultivating moral values to fortify itself from the negative excesses of globalization. But the most important thing is how the moral values that have been invested in Islamic education are able to act as a liberating force from the crush of poverty, ignorance and socio-cultural and economic backwardness. This paper aims to explore the role of Islamic education in public social education which is the main foundation of a nation's development.